Evolution of morphology and multiferroic properties of polycrystalline erbium manganite synthesized via mechanical alloying - Noor Ismail, Muhammad Aizat (2014)
In this research work, the goal is to establish the parallel evolution stages of microstructure development and properties development and their relationship. This kind of observation is absent in the literature since for several past decades, studies of the relationship between morphological properties and ferroelectric and dielectric properties of multiferroic materials have been focusing only on the product of the final sintering temperature, largely neglecting the parallel evolutions of morphological and properties and their relationship at various sintering temperatures. Erbium manganese oxide was prepared via high-energy ball milling (HEBM) in a hardened steel vial for 12 hours using a SPEX8000D mill. To get the evolving series of temperature, the pellet samples went through multi-sample sintering, where the samples were sintered from 600°C to 1200°C with 50°C increments, for any one sample being subjected to only one sintering temperature. The x-ray diffraction (XRD) results confirm the formation of the crystalline sample in an evolution series of ErMnO3. The evolution of microstructural properties was studied using FEI NovaNano 230 FeSEM. The dielectric studies were carried out by using an Agilent Impedance Analyzer Model 4291B. For ferroelectric transition temperature and P-E hysteresis loop was measured using a typical LCR meter induced 4284A with VECSTAR furnace and a Precision LC from Radiant Technologies respectively. The XRD patterns showed an improvement of crystallinity with increasing sintering temperature. At 700°C sintering temperature, single phase material (ErMnO3) starting to appear until 950°C and as at 950°C sintering temperature was known as the optimum crystallization temperature for ErMnO3. As degree of crystallinity increase with increasing sintering temperature, at final sintering temperature 1200°C, ErMnO3 peaks were the only observed with no other second phase peaks. SEM micrographs showed larger grain size as the sintering temperature increased, consequently increasing the multi-domain grains. For Polarization-Electric field (PE) plot reveals ErMnO3 is highly leaky ferroelectrics with P-E curve shape drastically different from the normal shape of highly insulating ferroelectrics. It shows the remanent polarization, the coercive field and dielectric constant generally decreased with increasing grain size. The dielectric studies on evolution microstructure for ErMnO3 showed that the resonant frequency increasing with grain size. However the ferroelectric transition temperature (TFE) which is intrinsic properties did not change during microstructure evolution. The value estimates by experimentally is ~ 580°C.